Ischaemic Necrosis of Pinnae in a Dachshund Dog – A Report - Nath, Krishna; Unny, N Madhavan; Pillai, Usha Narayan (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Ischaemic necrosis or thrombo-vascular necrosis of pinnae or pinnal margin vasculopathy is a slowly progressive idiopathic  syndrome characterized by wedge-shaped devitalization and  necrosis of the distal pinnae. It may occur either in unilateral  or bilateral forms, bilateral affection being more common.  Initially, an erythematous swelling and discoloration may be  noted in the center of the medial aspect towards the apex  of pinnae. Later, a necrotic ulcer may be seen in the center  of the lesion, progressing to exudation and hemorrhage.  In chronic cases, the areas of ulceration undergo complete  necrosis resulting in deformity. Although there is no age, sex,  and breed predisposition, certain breeds like Dachshunds and  Chihuahuas are commonly affected (Morris et al., 2013; Nuttall  et al., 2005). This communication reports a case of ischaemic  necrosis of pinnae in a Dachshund dog with its successful  clinical management.
Keywords: Clinical management; Dog; Pinna; Ischaemic necrosis